A Certain Kind of Freedom - Koutsomichalis, Marinos (My University, 2024)
Part soundwalk, part performance art, part punk archaeology, part getting lost in the dark: Άφρικα: A Certain Kind of Freedom is pivoting on artistic exploration and re-interpretation of a 'difficult' recent past. In part soundwalk, in part performance art, in part punk archaeology, in part getting lost in the dark; the work is a nocturnal rumination bringing together historical bewilderedness with first-person embodied experience of a place. The artist leads a night walk towards and inwards Agios Achillios island in Small Prespa Lake in Greece – near the borders of Albania, and North Macedonia – and back. En route, the walking audience is exposed to wildlife sounds and animal vocalisations, to orchestrated drama, and to historical records directly or indirectly concerning the broader geographical area and its significance during the Greek civil war.